How to mitigate budgetary slack? Learning from religiosity and participative budgeting - Desriani, Neny; Muhaqo, Niki Nawa; Panjaitan, Januar; Mirza, Aryan Danil; Sukmasari, Dewi (Proceeding International Conference on Accounting and Finance, 2024)
Budgetary slack is a potential hazard that emerges during the execution of the budgeting process. In the budgeting process, the involvement of each organizational unit is important to contribute to budget creation, because it provides more relevant field-related information. However, there is a tendency for subordinates to provide information that is biased for personal interests so that their participation can cause budgetary slack. This research aims to find out how to mitigate budgetary slack through participative budgeting and religiosity as well as how obstacles to participative budgeting and religiosity factors exist within the entity. This study employs qualitative research methodology by conducting literature study. This type of research gives researchers the freedom to search for and use library materials related to this research. The study findings demonstrate that the occurrence of budgetary slack during the budgeting process can be reduced and alleviated by instilling moral principles through the incorporation of religious values in every organizational division. So, participative budgeting for each organizational unit will lead to real information that can create an efficient and optimal budget so that budgetary slack does not occur and support the achievement of organizational goals.